2022
DOI: 10.1002/anie.202203893
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Fingerprints of Cavity Formation and Solute Insertion as a Measure of Hydration Entropic Loss and Enthalpic Gain

Abstract: Hydration free energies are dictated by a subtle balance of hydrophobic and hydrophilic interactions. We present here a spectroscopic approach, which gives direct access to the two main contributions: Using THz-spectroscopy to probe the frequency range of the intermolecular stretch (150-200 cm À 1 ) and the hindered rotations (450-600 cm À 1 ), the local contributions due to cavity formation and hydrophilic interactions can be traced back. We show that via THz calorimetry these fingerprints can be correlated 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
88
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(97 citation statements)
references
References 53 publications
8
88
1
Order By: Relevance
“…Whereas for water at hydrophobic surfaces the librational band is expected to blue-shift as a consequence of steric hindrance, 91 here both librational modes (L1 and L2) are found to be red-shifted with respect to those found in bulk water, as also observed experimentally for water confined in micelles 92 and for water droplets at the interface with a graphene surface. 93 Moreover, a population increase in the hard-librations and a loss in population of soft-librations at d int = 0.8 nm is highlighted by the steeper slope of the librational band 80 between 350 and 650 cm −1 with respect to the systems at d int = 1.0 and 1.4 nm, as observed in Fig. 2.…”
Section: Experimental Thz Spectra: Dissection and Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Whereas for water at hydrophobic surfaces the librational band is expected to blue-shift as a consequence of steric hindrance, 91 here both librational modes (L1 and L2) are found to be red-shifted with respect to those found in bulk water, as also observed experimentally for water confined in micelles 92 and for water droplets at the interface with a graphene surface. 93 Moreover, a population increase in the hard-librations and a loss in population of soft-librations at d int = 0.8 nm is highlighted by the steeper slope of the librational band 80 between 350 and 650 cm −1 with respect to the systems at d int = 1.0 and 1.4 nm, as observed in Fig. 2.…”
Section: Experimental Thz Spectra: Dissection and Discussionmentioning
confidence: 59%
“…Based on the computational analysis in particular of the bilayer system S, the resonance at about 150 cm À1 could be assigned to H-bonds within the water layers close to the interface with graphene. The frequency resembles thus the first hydration layer of model hydrophobic solutes [78][79][80] and boron nitride surfaces, 81 denoted as a two-dimensional H-bond network (''H-bond wrap''), and in confined water within reverse micelles. 82 Furthermore, we experimentally observe the ST3 band at 235-245 cm À1 .…”
Section: Experimental Thz Spectra: Dissection and Discussionmentioning
confidence: 99%
“…Thus, such amplitudes can be directly correlated with thermodynamic quantities, as we demonstrated in our recent works, ,, overcoming the limits of surface-scaling and residue-additivity approximations. This is the core of our THz-calorimetry approach . Exploiting such thermodynamics–spectroscopy correlation, we aim to rationalize the free energy contributions from hydrophobic and hydrophilic solvation based on well-defined experimental observables in real time, while LLPS is monitored.…”
mentioning
confidence: 74%
“…Although our calculations miss important contributions in terms of entropic effects and cavity formation, 80 it can be concluded that enthalpic interactions 32,52 in terms of charge transfer mechanisms between different amino acids and water molecules are rather comparable. Such findings may provide a rationale why single point mutations that affect the primary structure of proteins do not significantly change the structural properties.…”
Section: Amino Acidsmentioning
confidence: 78%